Liver abscess caused by Serratia grimesii in an immunocompetent patient - Balakrishna, Arjun M.; Mahto, Subodh K.; Goel, Mishita; Goel, Atul; Mitrolia, Bobby (International Journal of Research in Medical Sciences, 2018)
In tropical and subtropical countries, the most common cause of liver abscess is Entamoeba histolytica. However, pyogenic infections are common due to bacteria like Kleibsella pneumonia followed by Escherichchia coli and enterococcus species. The possibility of atypical organisms should be considered especially with recurrent liver abscess. We report a case of recurrent liver abscess caused by Serratia grimesii in an immunocopetent individual. Early isolation of the organism along with drug susceptibility testing would make a marked difference in improving the management of the patient and associated prognosis.